Tri-polarity structure and the Post-Cold War Asia Pacific Regional politics - Mohd. Noor Yazid (Primrose Hall Publishing Group, 2020)
This paper discusses the tri-polarity structure (of the United States, the Soviet Union and China) from 1971 until 1991 and the impact on post-Cold War Asia Pacific regional politics. The objectives of the paper are threefold: First, to explain how important the tri-polarity structure is to regional politics of the Asia Pacific; Second, to discuss the relationship of the tri-polarity structure (1971-1991) and the regional political structure after the end of the Cold War, and; Third, to analyse the relationship of the rising and China’s strong economic position and the tri-polarity structure. This paper concludes that the tri-polarity structure was an important and influence to the regional political structure of the Asia Pacific after the end of the Cold War. Without tri-polarity structure, it would have been impossible for China to achieve very rapid economic development in the 1980s and 1990s and pave the way to become the second largest global economy at the end of 2010. Without economic strength, it would have been impossible for China to become a strong military power. The strong position of China in politics (military) and economics influenced the regional political structure of the Asia Pacific. It would not have had the same impact if it had become a unipolar political structure, as in Europe after the collapse of the Soviet Union in 1991.